2011
DOI: 10.1371/journal.pone.0029168
|View full text |Cite
|
Sign up to set email alerts
|

A Genome-Wide Association Study of the Protein C Anticoagulant Pathway

Abstract: The Protein C anticoagulant pathway regulates blood coagulation by preventing the inadequate formation of thrombi. It has two main plasma components: protein C and protein S. Individuals with protein C or protein S deficiency present a dramatically increased incidence of thromboembolic disorders. Here, we present the results of a genome-wide association study (GWAS) for protein C and protein S plasma levels in a set of extended pedigrees from the Genetic Analysis of Idiopathic Thrombophilia (GAIT) Project. A t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 36 publications
2
25
0
Order By: Relevance
“…The four variants, rs10493374, rs12032616, rs17127529 and rs6679032, with modest associations were located in and around the DNAJC6 locus. A previous GWAS of the anticoagulant pathway also detected significant associations between certain SNPs in the DNAJC6 gene and free protein S plasma levels (27). The protein C anticoagulant pathway regulates blood coagulation by preventing the formation of thrombi.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…The four variants, rs10493374, rs12032616, rs17127529 and rs6679032, with modest associations were located in and around the DNAJC6 locus. A previous GWAS of the anticoagulant pathway also detected significant associations between certain SNPs in the DNAJC6 gene and free protein S plasma levels (27). The protein C anticoagulant pathway regulates blood coagulation by preventing the formation of thrombi.…”
Section: Discussionmentioning
confidence: 85%
“…The protein C anticoagulant pathway regulates blood coagulation by preventing the formation of thrombi. This pathway has two main plasma components, protein C and protein S. Deficiencies in antithrombin, protein C and protein S, or an impaired anticoagulant pathway, increase the incidence of thromboembolic disorders (27). Notably, a number of researchers have suggested that intravascular coagulation and microcirculatory thrombotic occlusion may provide a common pathway to non-traumatic osteonecrosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The first nationwide survey for pediatric thrombophilia in Japan suggested a higher prevalence of PC deficiency than expected (24,25). The discrepancy may be explained by the wider range of PC activity than that of PS or AT activity in infant and children (18,26), partly arising from the inherent variation of PC pathway (27,28). Clinical manifestation and thrombin generation differ among the family members having the same PROC mutation (29).…”
Section: Discussionmentioning
confidence: 99%
“…Human protein C (PC), a 62-kDa vitamin K-dependent zymogen of serine protease, is a glycoprotein mainly synthesized in the liver (Kisiel, 1979;Athanasiadis et al, 2011). Its structure is similar to other vitamin K-dependent proteins that affect blood clotting, such as factor II, VII, IX, and X.…”
Section: Introductionmentioning
confidence: 99%